PENENTUAN BIDANG MINAT MAHASISWA MENGGUNAKAN METODE TOPSIS BERBASIS SISTEM PENDUKUNG KEPUTUSAN DINAMIS - Lexi Handi Nayana; Arya Abimanyu; Muhammad Nasyithul Ibad; Muhammad Ammarullah Ridho (Jurnal Ilmiah Informatika, 2020)
The selection process of the field of the interest of students majoring in Informatics Engineering at UIN Maulana Malik Ibrahim Malang at this time is still manually that is choosing to accord to the wishes of the students themselves, so that it is sometimes not in accordance with the values obtained. Therefore, a new method is needed, namely the Decision Making System for the selection process of interest. The method for overcoming this problem uses the TOPSIS method, where the TOPSIS method has a concept if the chosen alternative is the best alternative by considering various criteria. The research methods used include data collection methods and system development methods. The design of this application was made using UML, for the program using the PHP programming language, and for the database using the MySQL database program. Interest Decision Support System in the Department of Informatics has been successfully created with the TOPSIS method that has been implemented in the make decision support systems. In this decision support system, the accuracy value using the TOPSIS method is 67%, the recall value is 86%, the precision value is 86% and the f-measure is 86%.